Politikai mezők a posztkommunista átmenet korszakában: A pártok és a társadalmi osztályok a magyar politikában (1989-90) (Szociológiai Szemle, 2024)
In February 1989 the Hungarian Socialist Workers Party agreed to adopt a multi-party system. Within thirteen months free elections were held giving rise to a multi-faceted political system . Six parties had candidates elected to Parliament. These parties were situated in different political ‘fields’ according to the nature of their programmes and the predicted social composition of their constituencies. The paper attempts to describe the social characteristics of the actors and the nature of their struggle in these political fields. It claims that since 1989 the countries of Central Europe have embarked on the post-communist phase of development by eliminating the three major supports of the societies formerly called ‘communist’ or ‘state socialist’: the dominance of state ownership, party monopoly, and the cadre hierarchy. The evolution of three political fields has been posited for the period of post-communist transition: a national Christian centre-right, a liberal, and a social democratic field.The elections in March and April 1990 brought a massive victory for the national Christian parties. They won almost 68 percent of the seats, while the liberals received a mere third, and the Socialist Party, the only ‘leftist’ party to get into Parliament, received less than ten percent. The elections in 1990 also produced similar results in other countries of the region. This apparent return of the characteristics of the past is one of the most important problems discussed in the paper. Political sociologists usually assume a relation between political behaviour and social structure. Thus, the political sociologist is puzzled to find such an obstinate return of the status quo ante. What accounts for the weak explanatory force of the social structure and a persistent survival of the old political culture?In answering these questions, the authors first outline a hypothetical map of classes in post-communist society, confront their hypothesis with public opinion poll results, and then proceed to analyze voters’ and non-voters’ attitudes. The final section of their paper offers an institutionalist analysis of Central European politics. It explores why no party could ‘address’ the half or one-third of the voters who maintain predictably centre-left preferences.The authors conclude that although a considerable social democratic constituency exists which could support a political movement representing a leftist alternative to the national Christian governm ent policy, as yet no political party has been able to lend authentic expression to their interests. The future of Hungarian politics largely depends on whether this distortion of institution-building can be corrected, and whether the ensuing political vacuum can be eliminated. In Hungarian and, in general Central European politics, this situation presents real danger. If the left is unable to mobilize this constituency at a time of economic crisis and growing unemployment, it is to be feared that a ‘political entrepreneur’ standing to the right of the present government might address and win over the thus far silent majority in Hungarian political life.